Ultrasonographic evaluation of the conceptus from days 10 to 60 of pregnancy in jennies - Meira, Cezinande de [UNESP]; Ferreira, JCP; Papa, Frederico Ozanam [UNESP]; Henry, M. (Elsevier B.V., 1998)
Daily ultrasound examinations were conducted from Days 10 to 60 (ovulation = Day 0) of pregnancy to monitor the conceptus in jennies (n = 12). The embryonic vesicle was first detected on Day 11.5 +/- 0.9 (mean +/- SD; range 10 to 13d) and was mobile until movement ceased (fixation) on Day 15.5 +/- 1.4 (range, 13 to 18d). The vesicle was spherical from Days 10 to 18 (mean growth rate, 3.2 mm/d), non spherical (irregular) with a reduced growth rate (0.5 mm/d) from Days 19 to 29, and then grew at a moderate rate (1.6 mm/d) up to Day 46. on average, detection of the embryo proper (consistently located on the ventral aspect of the yolk sac) and embryonic heartbeat were Days 20.7 +/- 1.2 and 23.5 +/- 1.3, respectively. Formation of the allantoic sac was first detected on Day 24.4 +/- 1.7 and was complete on Day 36.8 +/- 1.6. Descent of the fetus (and formation of the umbilical cord) began on Day 37.9 +/- 1.7 and was complete on Day 44.1 +/- 2.1. Crown-ramp length averaged 3.7, 15.4, 22.7, 37.5 and 59.6 mm on Days 20, 30, 40, 50 and 60, respectively. In general, morphologic features and dates of occurrence were similar to those reported previously in the mare. (C) 1998 by Elsevier B.V.
Keywords: conceptus; embryo; donkey; pregnancy; ultrasonography